Local Ecological Knowledge on Climate Change and Ecosystem-Based Adaptation Strategies Promote Resilience in the Middle Zambezi Biosphere Reserve, Zimbabwe. (11th March 2019) - Kupika, Olga Laiza; Gandiwa, Edson; Nhamo, Godwell; Kativu, Shakkie
Abstract : Understanding local community perceptions on impacts, causes, and responses to climate change is vital for promotion of community resilience towards climate change. This study explored local ecological knowledge (LEK) held by local communities on climate change trends and impacts in the Middle Zambezi Biosphere Reserve (MZBR), Zimbabwe. The objectives of the study were to (i) investigate local community perceptions on trends and causes of climate change, (ii) identify biophysical impacts of climate change at the local level, and (iii) explore the ecosystem-based adaptation strategies towards climate change. The study used a mixed methods approach where a household questionnaire survey (n = 320 ), key informant interviews (n = 12 ), and focus group discussions (n = 8 ) were used to collect data between April 2015 and October 2016. Results from the study show that local communities have observed decreasing rainfall and increasing temperatures as key indicators of climate change. Local communities observed water scarcity, changes in vegetation phenology, livestock and wildlife mortalities, and food shortages due to drought as the major impacts on their livelihoods. LEK can contribute to adaptive management strategies that enhance resilience of socioecological systems (SES) in the face of climate change by providing information on the status and use of biophysical components of the environment and by highlighting potential local adaptation strategies that can sustain key livelihood practices.